'Candidatus Phytoplasma stylosanthis', a novel taxon with a diverse host range in Australia, characterised using multilocus sequence analysis of 16S rRNA, secA, tuf, and rp genes. Issue 1 (8th January 2021) - Rodrigues Jardim, Bianca; Kinoti, Wycliff M.; Tran-Nguyen, Lucy T. T.; Gambley, Cherie; Rodoni, Brendan; Constable, Fiona E.
Abstract : In Australia, Stylosanthes little leaf (StLL) phytoplasma has been detected in Stylosanthes scabra Vogel, Arachis pintoi Krapov, Saccharum officinarum L., Carica papaya L., Medicago sativa L., and Solanum tuberosum L. The 16S rRNA gene sequence of StLL phytoplasma strains from S. scabra, C. papaya, S. officinarum and S. tuberosum were compared and share 99.93–100 % nucleotide sequence identity. Phylogenetic comparisons between the 16S rRNA genes of StLL phytoplasma and other ' Candidatus Phytoplasma' species indicate that StLL represents a distinct phytoplasma lineage. It shares its most recent known ancestry with ' Ca . Phytoplasma luffae' (16SrVIII-A), with which it has 97.17–97.25 % nucleotide identity. In silico RFLP analysis of the 16S rRNA amplicon using i PhyClassifier indicate that StLL phytoplasmas have a unique pattern (similarity coefficient below 0.85) that is most similar to that of 'Ca . Phytoplasma luffae'. The unique in silico RFLP patterns were confirmed in vitro . Nucleotide sequences of genes that are more variable than the 16S rRNA gene, namely tuf (tu-elongation factor), secA (partial translocation gene), and the partial ribosomal protein ( rp ) gene operon ( rps19-rpl22-rps3 ), produced phylogenetic trees with similar branching patterns to the 16S rRNA gene tree. Sequence comparisons between the StLL 16S rRNA spacer region confirmed previous reports of rrn interoperon sequence heterogeneity for StLL, where the spacer region of rrnB encodes a complete tRNA-Isoleucine gene and the rrnA spacer region does not. Together these results suggest that the Australian phytoplasma, StLL, is unique according to the International Organization for Mycoplasmology (IRPCM) recommendations. The novel taxon ' Ca . Phytoplasma stylosanthis' is proposed, with the most recent strain from a potato crop in Victoria, Australia, serving as the reference strain (deposited in the Victorian Plant Pathology Herbarium as VPRI 43683).